성장혼합모형을 적용한 유아기 외현화 행동문제 발달궤적 유형에 따른 초등학교 1학년의 학교적응과 실행기능 곤란 - 김선희(Sunhee Kim) (Korean Journal of child studies, 2018)
Objective: This study examined types of trajectories for externalizing behavior problems from 4-6 year olds and differences in school adjustment and executive function difficulties of first-grade children for elementary school by types of trajectories for externalizing behavior problems. Methods: The 2012-2015 data of Panel Study on Korean Children (PSKC) were used. The sample for this analysis was 1518 children and their mothers and teachers participated from the first (2012) to the fifth (2015) years. Data was analyzed using growth mixture modeling. Results: First, externalizing behavior problems from 4-6 year olds showed linearly decreasing change over time. Second, four distinct latent classes of externalizing behavior problems for young children were found (low-decreasing trajectory, high-stable trajectory, moderate-increasing trajectory, and high-decreasing trajectory). Finally, there were differences the level of school adjustment and executive function difficulties by four distinct latent classes of externalizing behavior problems. Young children were on high-stable trajectory showed the lowest level of school adjustment and the highest level of executive function difficulties, while young children were on low-decreasing trajectory showed the highest level of school adjustment and the lowest level of executive function difficulties. These result showed that four distinct trajectories for externalizing behavior problems from 4-6 year olds was closely related to school adjustment and executive function difficulties of the first-grade children for elementary school. Conclusion: Finding suggest the importance of the early intervention on young children’s behavior problems grounded by four distinct latent classes of externalizing behavior problems for young children. KCI Citation Count: 16